2021
DOI: 10.7759/cureus.17606
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acne Vulgaris by Topical Spironolactone Solution Compared With Clindamycin Solution

Abstract: Background: Acne vulgaris is a common skin problem that is encountered in daily clinical work, affecting mostly the adolescent and young adult age group. Many topical therapies have been used in the treatment of mild to moderate types of acne vulgaris. However, none of these modalities is uniformly effective; furthermore, acne vulgaris is also associated with relapse and many topical side effects.Objective: To compare the effectiveness and side effects of topical 2% spironolactone solution and 1.5% clindamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(41 citation statements)
references
References 16 publications
(23 reference statements)
0
41
0
Order By: Relevance
“…Walton et al 19 did not have adequate data to assess the outcome. Afzali et al, Keladari et al, Naoimi et al, and Ayatollahi et al adequately reported their outcomes, but Walton et al did not have the available data for the reported results 15–19 . All five of the included studies had clear‐cut inclusion and exclusion criteria 15–19 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Walton et al 19 did not have adequate data to assess the outcome. Afzali et al, Keladari et al, Naoimi et al, and Ayatollahi et al adequately reported their outcomes, but Walton et al did not have the available data for the reported results 15–19 . All five of the included studies had clear‐cut inclusion and exclusion criteria 15–19 .…”
Section: Resultsmentioning
confidence: 99%
“…Three of the included trials assessed the effects of topical spironolactone supplements on skin conditions including skin redness, sebum, moisture, dryness, sensitivity, melanin, elasticity, and pH levels among the individuals 15,18,19 . Only one study evaluated the patient satisfaction rate with topical spironolactone in comparison to placebo 16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one small single-blinded study, topical spironolactone 2% solution was shown to significantly reduce comedone count compared to no effect on comedones by clindamycin. 14 Additionally, compared to clindamycin, the topical application of spironolactone resulted in a more significant reduction of patients’ Acne Severity Index (ASI). Similar results have been achieved in other clinical trials.…”
Section: Introductionmentioning
confidence: 99%